Developing the EFL Teaching Process through Electronic Teaching- Portfolios Tech... - Salima MAOUCHE, (مجلة الآداب و العلوم الإجتماعية, 2012)
This paper explores and examines the role the Electronic Teaching Portfolios on developing the EFL teaching process in secondary schools in Bejaia. For this aim, important considerations have to be taken because we strongly believe that these tools if introduced and implemented by EFL teachers, they can not only serve as developmental and summative assessments for teachers, but they can also contribute in the conceptual experience in developing the teaching process as well. Therefore, the data collected through the teachers’ questionnaire enable us to conduct our investigative work in order to determine areas of strengths and weaknesses in teaching and thus, help promote the teachers’ practices and methods. The general research questions directed in the present study are: (1) - How can web-based teaching portfolios bridge the gap between two parties typically not communicating with one another in order to promote the teaching practices? (2) – Do the web-based teaching portfolios prove to be effective tools with which to solicit participation of faculty and teaching staff towards progress? Hence, this article is divided into four parts which are as follows: the first part provides an overview on the process of developing the teaching as a craft, and teachers as professionals. The second part sheds light on the suggested tools and the importance they have on developing the target points. The third part is devoted to analysing and interpreting the data gathered. The forth part is however, devised to provide our readers with constructive recommendations and answers to the research questions posed.